2015
DOI: 10.3109/13880209.2015.1068337
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated metabolites represent the major circulating forms ofAbelmoschus manihot in vivoand show an altered pharmacokinetic profile in renal pathology

Abstract: Objective: Flavonoids are main active components of A. manihot, which can be transformed into glucuronide/sulfate conjugates in vivo. Exploring the pharmacokinetic profile of these conjugates is necessary to further elucidate the mechanism of action. Material and method: Flavonoid fraction of A. manihot (FFA) was extracted from A. manihot flower with ethanol. FFA (400 mg/kg) was orally given to normal rats and chronic kidney disease (CKD) model rats. Blood samples were collected at 5, 15, 30, 45, 60, 90, 120, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…Therefore, they can be used for standardization of AM production [20, 21]. Recent studies have indicated that flavonoids can be converted to a combination of acid sulfates in animals, which may be the main active metabolic ingredient for kidney protection [22]. For the mechanistic studies, AM has shown to improve kidney inflammation and glomerular injury in rats with doxorubicin-induced nephropathy through inhibition of the p38 MAPK signaling pathway and TGF-β1 protein expression [23].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they can be used for standardization of AM production [20, 21]. Recent studies have indicated that flavonoids can be converted to a combination of acid sulfates in animals, which may be the main active metabolic ingredient for kidney protection [22]. For the mechanistic studies, AM has shown to improve kidney inflammation and glomerular injury in rats with doxorubicin-induced nephropathy through inhibition of the p38 MAPK signaling pathway and TGF-β1 protein expression [23].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, aglycones exhibited potentiated cytotoxicity compared to their glycosides. Recently, it has been suggested that aglycones and glycosides exhibit different pharmacokinetic profile resulting in altered biological efficacy (Guo et al, 2015). Therefore, it is necessary to compare the biological properties of glycosides compared to their aglycones.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids, the primary active components of Flos A. manihot , can be transformed into glucuronide–sulphate conjugates in vivo . The pharmacokinetic profile of these conjugates is of considerable importance to the renoprotective effect of Flos A. manihot in vivo .…”
Section: Introductionmentioning
confidence: 96%
“…The pharmacokinetic profile of these conjugates is of considerable importance to the renoprotective effect of Flos A. manihot in vivo . The pharmacokinetic profile of conjugated metabolites of Flos A. manihot has been evaluated in normal rats and in adriamycin‐induced CKD rats using UPLC‐MS . In that study, the glucuronide–sulphate conjugates were the major metabolites of Flos A. manihot in normal rats and these metabolites may contribute to the renoprotective effects of Flos A. manihot in vivo .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation